Reconstruction of Child Custody Rights After Divorce Based on Maqashid Syariah and the Best Interest of the Child - Kroniko, Hendri; A, Efizal; Mustafa, Ali (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Divorce has a significant impact on the fulfillment of children's rights and well-being, while custody decisions are often normative and do not take into account the child's best interests. Therefore, this study aims to reconstruct the concept of post-divorce child custody by integrating the maqāṣid al-syarī‘ah and the principle of the best interest of the child. The research method employed is a qualitative normative approach with a maqasid sharia perspective, based on a literature study. Primary data sources include classical fiqh books and contemporary Islamic legal literature that discuss hadith. Secondary data sources include scientific books, national and international journal articles, previous research results, and laws and regulations related to child custody after divorce, such as the Compilation of Islamic Law (KHI) and the Indonesian Marriage Law. Data were collected through documentation and analyzed using descriptive analytical techniques. Post-divorce child custody reconstruction needs to be built on the integration of the maqāṣid al-syarī‘ah (the principles of Islamic law) and the principle of the best interest of the child as the primary basis for determining custody. This approach prioritizes the child's well-being, taking into account religious, psychological, emotional, educational, and social aspects. Thus, custody determination is not merely normative, but contextual and equitable. This is expected to result in more humane decisions oriented toward the child's protection and future.